Review of ICESat and ICESat-2 literature to enhance applications discovery - Brown, Molly E.; Arias, Sabrina Delgado; Chesnes, Michael (Remote sensing applications, 2023)
Altimeter data from the first- and second-generation NASA Ice, Cloud and land Elevation (ICESat) satellite missions has the potential to transform a variety of key applications through improved decision making such as ocean navigation, surface water monitoring, and wildland fuels assessments. Here we review the literature using ICESat and ICESat-2 data to identify applications-relevant literature, defined as research that can lead to the use of data products in decision-making, policy making or risk reduction activity for societal benefit. We used the scholarly database ProQuest to identify bibliographic citations which were likely to lead to applications and user communities of data from the ICESat and ICESat-2 satellite lidar missions. We use the network visualization software tool Quid to create visual representation of clusters according to the textual similarity of their abstracts. We then text mine the NASA Applied Sciences Project Portfolio website to identify applications-relevant keywords and use these in combination with Quid-generated terms to create subsets of the literature according to how likely it was to lead to an application. Visualizations generated using the Quid software are presented separately for both ICESat and ICESat-2. We found an overall increase in the number of applications-relevant publications for ICESat-2 when comparing publications in the first four years after launch for both missions. This increase may be attributable to sustained efforts by the mission to reach out to the scientific and stakeholder communities during the pre-launch phase and to significant efforts by the mission to facilitate access to the data. However, our discovery of the literature also revealed a markedly low number of publications demonstrating actual applications of both ICESat and ICESat-2 data. We conclude that there is a need to cultivate a culture in academia that values linking science with use. We also identify multiple applications-relevant research where future applications efforts could focus. •Literature review that extracted applications-relevant ICESat and ICESat-2 research.•Compared ICESat and ICESat-2 research with societal relevance.•Created a network diagram for subject-relevant terms for both sensors.•Stakeholder engagement accelerates societally relevant research.